Designing and Building Go-Karts As An Engineering Student Project - Hassan, Muhammad Zahir; Shamsudin, Shamsul Anuar (2005)
This paper describes a semester project carried out by the automotive students within the Faculty of Mechanical Engineering at Kolej Universiti Teknikal Kebangsaan Malaysia (KUTKM)to fulfill the requirement of the Vehicle Dynamics module coursework. The students were required to design and develop their own rally go-kart. This allowed them to apply theoretical knowledge that they have acquired into practical work with their own creativity when designing chassis, suspension system, braking system and steering system. The project essentially had three main parts. Initial study concentrated on the design and analysis of the go-kart using a modern computer aided engineering software, CATIA. The second part of the project is the stage of building the go-kart. Lastly, the final stage was the go-karts had to compete on a racing track. The evaluation of the project was based on the design and analysis of the go-kart using CAD and FEA packages, building process, technical report and also performance during the racing events. The finite element analysis phase of this project is presented here although this is well established in both education and industry. Also described in this paper is the engineering and manufacturing task as well as costing for this project.